1972
DOI: 10.1677/joe.0.0550387
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS OF HUMAN CHORIONIC GONADOTROPHIN IN VITRO: INCORPORATION OF [14C]l-LEUCINE

Abstract: Fresh human placental tissue from first trimester pregnancies was incubated with [14C]l-leucine and the incorporation of the labelled amino acid into placental proteins was studied in both the soluble and the particulate fractions. Free [14C]l-leucine was completely separated from labelled proteins by exhaustive dialysis. This was confirmed by Sephadex G-100 gel chromatography.In preliminary experiments, the total protein fraction from Sephadex was submitted to polyacrylamide gel electrophoresis; columns divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This correlation has suggested to some that hCG is transported from the maternal circulation through the chorion-amnion and directly into amniotic fluid (31). Maximal hCG production by the placenta occurs at 4-10 weeks of gestation (32,33), after which the maternal serum hCG concentration slowly declines (30). At about the 9th week of gestation, however, amniotic fluid hCG levels rise gradually to peak during the 13th or 14th week (28), becoming at least 10-fold greater than those in umbilical cord blood (27).…”
Section: Discussionmentioning
confidence: 99%
“…This correlation has suggested to some that hCG is transported from the maternal circulation through the chorion-amnion and directly into amniotic fluid (31). Maximal hCG production by the placenta occurs at 4-10 weeks of gestation (32,33), after which the maternal serum hCG concentration slowly declines (30). At about the 9th week of gestation, however, amniotic fluid hCG levels rise gradually to peak during the 13th or 14th week (28), becoming at least 10-fold greater than those in umbilical cord blood (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the biosynthesis in vitro of hCG from placenta was also confirmed using 3H-proline as a radioactive precursor . Up to this time, however, there has been no report which detected the presence of radioimmunological FSH activity in the medium of tissue culture of chorionic tissue although some workers have tried to assay chorionic FSH activity by radioimmunoassay for pituitary FSH (Benagiano et al, 1972). The chorionic FSH activity in the cultured medium should be detected by anti-hCFSH serum since hCFSH did not cross-react with anti-FSH serum of pituitary origin in Ouchterlony immunodiffusion (Ashitaka et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Protein hormone synthesis by placenta is not well understood yet although there have been several reports available on the biosynthesis of hCG (Benagiano et al, 1972;Patrito et al, 1973;Tojo et al, 1974;Maruo et al, 1974) and on human placental lactogen (Friesen et al, 1968 These findings prompted us to study the incorporation in vitro of labeled amino acid into hCFSH.…”
Section: Synopsismentioning
confidence: 99%
“…The synthesis of hCG was greater in pla centas of 4-6 weeks gestation than in placentas of 14-18 weeks of gesta tion. Benagiano et al [49] carried out similar incubations, separated the peptides synthesized by gel filtration on Sephadex G-100, and found that the fractions that had the greatest radioactivity also showed the greatest hCG activity by radioimmunoassy. This demonstrated that tissue from first trimester placentas actively synthesizes human chorionic gonadotro pin.…”
mentioning
confidence: 99%